2004
DOI: 10.1063/1.1758297
|View full text |Cite
|
Sign up to set email alerts
|

Formation of SiGe nanocrystals in HfO2 using in situ chemical vapor deposition for memory applications

Abstract: The in situ deposition process of SiGe nanocrystals on SiO2 and HfO2 substrates was studied using Auger electron spectroscopy, atomic force microscopy, and x-ray photoelectron spectroscopy. The Ge concentration in SiGe nanocrystals increased with deposition time at equal Si/Ge flow rates. Analysis indicated that the nucleation of Ge takes place preferentially on prenucleated Si on the dielectric. Memory transistors were fabricated using SiGe nanocrystals and HfO2 tunneling/control dielectrics as a gate stack. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
12
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(12 citation statements)
references
References 7 publications
0
12
0
Order By: Relevance
“…Although Ge-incorporated HfON has been proposed to enhance the charge-trapping capability for nonvolatile memory [20], most Ge-related materials for charge-trapping applications are pertinent to nanocrystal-based trapping media. Nanocrystal-based memory devices indeed exhibit prominent electrical performance [21]- [26]; however, controlling the size and uniformity of nanocrystals is still a challenge that needs to be overcome. Ge 3 N 4 , which was formed by ammonia (NH 3 ) plasma nitridation of an amorphous Ge film in this study, has demonstrated great potential for advanced flash memory application in terms of a large memory window, highspeed operation as well as robust endurance and satisfactory retention.…”
Section: Introductionmentioning
confidence: 99%
“…Although Ge-incorporated HfON has been proposed to enhance the charge-trapping capability for nonvolatile memory [20], most Ge-related materials for charge-trapping applications are pertinent to nanocrystal-based trapping media. Nanocrystal-based memory devices indeed exhibit prominent electrical performance [21]- [26]; however, controlling the size and uniformity of nanocrystals is still a challenge that needs to be overcome. Ge 3 N 4 , which was formed by ammonia (NH 3 ) plasma nitridation of an amorphous Ge film in this study, has demonstrated great potential for advanced flash memory application in terms of a large memory window, highspeed operation as well as robust endurance and satisfactory retention.…”
Section: Introductionmentioning
confidence: 99%
“…In thin film technology, chemical vapour deposition (CVD) is one of the versatile methods for depositing ultrathin films and works by thermal decomposition of precursors in a reaction chamber [12]. It is widely used for technological applications and manufacturing of industrial devices and it is suitable for batch and semicontinuous operations [13].…”
Section: Introductionmentioning
confidence: 99%
“…Many device applications were recently proposed (e.g., Si nanowire electrical interconnects [32,33], Si nanowire thermoelectric devices [34,35], Si nanowire sensors [36][37][38], SiGe cluster-based memory devices [39][40][41], SiGe cluster-based near-infrared light emitters [42][43][44][45][46], etc. ), and detailed understanding of thermal processes in these nanostructures is absolutely necessary.…”
mentioning
confidence: 99%